Sexual behaviour of men that consulted in medical outpatient clinics in Western Switzerland from 2005-2006: risk levels unknown to doctors? - Dubois-Arber Françoise; Meystre-Agustoni Giovanna; André Jeannin; De Heller Kim; Alain Pécoud; Bodenmann Patrick (BMC, 2010)
Abstract Background To determine male outpatient attenders' sexual behaviours, expectations and experience of talking about their sexuality and sexual health needs with a doctor. Methods A survey was conducted among all male patients aged 18-70, recruited from the two main medical outpatient clinics in Lausanne, Switzerland, in 2005-2006. The anonymous self-administered questionnaire included questions on sexual behaviour, HIV/STI information needs, expectations and experiences regarding discussion of sexual matters with a doctor. Results The response rate was 53.0% (N = 1452). The mean age was 37.7 years. Overall, 13.4% of patients were defined as at STI risk - i.e. having not consistently used condoms with casual partners in the last 6 months, or with a paid partner during the last intercourse - regarding their sexual behaviour in the last year. 90.9% would have liked their physician to ask them questions concerning their sexual life; only 61.4% had ever had such a discussion. The multivariate analysis showed that patients at risk tended to have the following characteristics: recruited from the HIV testing clinic, lived alone, declared no religion, had a low level of education, felt uninformed about HIV/AIDS, were younger, had had concurrent sexual partners in the last 12 months. However they were not more likely to have discussed sexual matters with their doctor than patients not at risk. Conclusion Recording the sexual history and advice on the prevention of the risks of STI should become routine practice for primary health care doctors.